Influence of organizational climate on teacher performance in nurses at a public university in Lima - Rivas Díaz, Luisa H. (2017)
OBJECTIVES: To evaluate the influence of the organizational climate on the performance of the Nursing teacher in National University of San Marcos. MATERIALS AND METHODS: T Descriptive, cross-sectional and correlational study. The sample was 45 teachers and 58 nursing students of the fifth year of studies. Likert scales instrument. RESULTS: Of a total of 45 teachers surveyed, 63% of teachers report an unhealthy or average organizational climate, and 54.9% of teachers, according to students, have an average level of performance. CONCLUSIONS:The organizational climate significantly influences the performance of the nursing teacher. Most teachers have an unhealthy organizational climate and an average level of teaching performance.